Cutting Wood Machine - Bassam, Odeh; Wael, Abu Gharbieh; Mahmoud, Abu Al Huda; Hamzah, Shawahany (My University, 2017)
Cutting wood machine is working on the cutting the wood regularly and smooth, Where the wood cutting longitudinally. It’s consist of three central department’s:- Design department , Control department , Cutting department. In the design department will be used hydraulic piston it pushes a piece of wood to blade’s and in this section it will be design the body of machine. Control department it will work on control in the vastness of the distance between blade’s in order to ensure cutting any piece of wood , No matter what the diameter. Cutting department consist’s of these blade’s, Which will work’s on wood cutting longitudinally.